Development of a new patient-derived xenograft humanised mouse model to study human-specific tumour microenvironment and immunotherapy. Issue 10 (30th March 2018) - Zhao, Yue; Shuen, Timothy Wai Ho; Toh, Tan Boon; Chan, Xue Ying; Liu, Min; Tan, Sue Yee; Fan, Yong; Yang, Hechuan; Lyer, Shridhar Ganpathi; Bonney, Glenn Kunnath; Loh, Eva; Chang, Kenneth Tou En; et al.
Abstract : Objective: As the current therapeutic strategies for human hepatocellular carcinoma (HCC) have been proven to have limited effectiveness, immunotherapy becomes a compelling way to tackle the disease. We aim to provide humanised mouse (humice) models for the understanding of the interaction between human cancer and immune system, particularly for human-specific drug testing. Design: Patient-derived xenograft tumours are established with type I human leucocyte antigen matched human immune system in NOD- scid Il2rg −/− (NSG) mice. The longitudinal changes of the tumour and immune responses as well as the efficacy of immune checkpoint inhibitors are investigated. Results: Similar to the clinical outcomes, the human immune system in our model is educated by the tumour and exhibits exhaustion phenotypes such as a significant declination of leucocyte numbers, upregulation of exhaustion markers and decreased the production of human proinflammatory cytokines. Notably, cytotoxic immune cells decreased more rapidly compared with other cell types. Tumour infiltrated T cells have much higher expression of exhaustion markers and lower cytokine production compared with peripheral T cells. In addition, tumour-associated macrophages and myeloid-derived suppressor cells are found to be highly enriched in the tumour microenvironment. Interestingly, the tumour also changes gene expression profiles in response to immune responses by upregulating immune checkpoint ligands. Most importantly, in contrast to the NSG model, our model demonstrates both therapeutic and side effects of immune checkpoint inhibitors pembrolizumab and ipilimumab. Conclusions: Our work provides a model for immune-oncology study and a useful parallel-to-human platform for anti-HCC drug testing, especially immunotherapy.